Carbon isotopic composition of intact branched GDGT core lipids in Greenland lake sediments and soils. (August 2017) - Colcord, Devon E.; Pearson, Ann; Brassell, Simon C.
Highlights: δ 13 C values of intact brGDGTs from lakes and soils were measured via SWiM-IRMS. Depletion of δ 13 CGDGTs relative to δ 13 CTOC supports a heterotrophic source for brGDGTs. Individual values for δ 13 CGDGT confirmed in situ brGDGT production in lakes. Abstract: Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are the basis of the MBT and CBT indices used as proxies for past changes in temperature and soil pH. Although these compounds were initially thought to originate solely from anaerobic soil bacteria, there is now convincing evidence that they are also produced within aquatic environments. However, the specific source organism(s) remain unknown. We utilize here spooling wire microcombustion-isotope ratio mass spectrometry (SWiM-IRMS) to measure the δ 13 C composition of intact brGDGTs from a series of lake sediments and soils, including samples exhibiting in situ production of brGDGTs. The results show close parallels between the δ 13 CbrGDGT values and OM in the downcore profiles for sediment sequences from two lakes. In addition, the δ 13 CbrGDGT values were consistently more negative than those of OM for the lakes and soil samples from the surrounding watershed. The values are consistent with a mixture of heterotrophic sources and preferential utilization of 13 C-depleted carbon sources. The δ 13 C values of individual brGDGT components confirm in situ production of brGDGTs within lacustrine dysoxic environments and suggest that their association with an elevated CH4 level during the summer may reflect methanotrophy.